2019
DOI: 10.3390/cancers11020149
|View full text |Cite
|
Sign up to set email alerts
|

Liver Kinase B1—A Potential Therapeutic Target in Hormone-Sensitive Breast Cancer in Older Women

Abstract: Background: The role of liver kinase B1 (LKB1), a serine/threonine kinase, has been described in the development of PeutzJagher’s syndrome, where a proportion (~45%) of patients have developed breast cancer in their lifetime. Cell line studies have linked LKB1 with oestrogen receptors (ER) and with the Adenosine monophosphate-activated protein kinase (AMPK) pathway for energy metabolism. However, limited studies have investigated protein expression of LKB1 in tumour tissues and its intracellular relationships.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
(48 reference statements)
3
8
0
Order By: Relevance
“…LKB1 is a tumour suppressor gene, of which there is little research in the setting of older women. Studies have shown that LKB1 can inhibit the aromatase enzyme with the AMP-activated protein kinase, supporting its potential role in prediction of response to primary endocrine therapy [32,33]. In a recent analysis of all patients undergoing surgery within the current cohort of older women described in this present study, older women had higher expression of LKB1 compared to a younger cohort [32].…”
Section: Correlation Of Biomarker Expression With Ttpsupporting
confidence: 68%
See 2 more Smart Citations
“…LKB1 is a tumour suppressor gene, of which there is little research in the setting of older women. Studies have shown that LKB1 can inhibit the aromatase enzyme with the AMP-activated protein kinase, supporting its potential role in prediction of response to primary endocrine therapy [32,33]. In a recent analysis of all patients undergoing surgery within the current cohort of older women described in this present study, older women had higher expression of LKB1 compared to a younger cohort [32].…”
Section: Correlation Of Biomarker Expression With Ttpsupporting
confidence: 68%
“…Studies have shown that LKB1 can inhibit the aromatase enzyme with the AMP-activated protein kinase, supporting its potential role in prediction of response to primary endocrine therapy [ 32 , 33 ]. In a recent analysis of all patients undergoing surgery within the current cohort of older women described in this present study, older women had higher expression of LKB1 compared to a younger cohort [ 32 ]. LKB1 expression was associated with better survival among patients receiving adjuvant endocrine therapy, but TTP was not reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies made a direct comparison between measurement of biomarkers in an older compared to a younger cohort (Table 1) [9,[16][17][18][19]. The remaining eight studies measured a biomarker in an older cohort alone (Table 2) [20][21][22][23][24][25][26][27].…”
Section: General Characteristics Of the Studiesmentioning
confidence: 99%
“…Given this, and other needs to appropriately select treatments, including primary and adjuvant therapies in this challenging population, biomarker studies play a very important role in translational research. Three such biomarkers-LKB1 [7] and cytoplasmic cyclin E [8] (poor prognostic in the older (>70 years) population), and HDAC5 [9] (poor prognostic in the very young (<35 years) patients)-have been found to be associated with age. Furthermore, other conventional and emerging prognostic and predictive factors were investigated and reported in this Special Issue.…”
mentioning
confidence: 99%